2018
DOI: 10.4102/sajcd.v65i1.591
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between video otoscopy and standard tympanometry findings in adults living with human immunodeficiency virus (HIV) in South Africa

Abstract: BackgroundLiterature suggests that there is a correlation between video otoscopy and standard tympanometry findings. However, there is limited evidence on whether these two measures are comparable in the identification of middle ear pathologies in adults living with human immunodeficiency virus (HIV).ObjectiveThis study aimed to determine the correlation between video otoscopy and standard tympanometry with 226 Hz probe tone in the identification of middle ear pathologies in adults living with HIV in Limpopo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 44 publications
1
38
1
Order By: Relevance
“…In a study by Sebothoma et al . (2018), agreement in diagnoses between two ENTs was high . Pinchichero reported that within cadres, the diagnoses were highly consistent, however, data were not provided on level of agreement .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sebothoma et al . (2018), agreement in diagnoses between two ENTs was high . Pinchichero reported that within cadres, the diagnoses were highly consistent, however, data were not provided on level of agreement .…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Despite these advancements, occurrence of middle ear pathologies seems to persist in individuals living with HIV. 11,12 Disorders of the auditory and vestibular system, including otitis media, are often associated with HIV/AIDS 13,14…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing evidence that suggests that HIV increases the risk of middle ear pathologies by causing the CD4 cell count to decline in the body and thus incapacitating the immune system, 15 allowing the viruses and bacteria to enter the middle ear system causing middle ear disorders. 16 Several studies have reported that otitis media with effusion (OME), serous otitis media (SOM), retracted tympanic membrane (TM) and perforated TM occur in adults with HIV, 12,16-18 and this has an influence in patients’ quality of lives.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of assessment may be improved using adjuvant tests such as pure-tone audiometry and tympanography; however, this requires the use of additional equipment and training for facilitators. None of the included studies looked specifically at the use of adjuvant investigations and whether this improved diagnostic concordance; however, Sebothoma et al [ 9 ] suggested that remote assessment of video-otoscopy plus tympanometry, is superior in identifying middle ear effusions compared to tympanometry alone. It could be suggested that the ability of remote assessment to answer the binary question of whether an examination is ‘normal’ or ‘abnormal’ is more important that its ability to distinguish between specific pathologies, as this is likely to be the trigger for further assessment by an otolaryngology specialist.…”
Section: Discussionmentioning
confidence: 99%